Prevenção da gravidez na adolescência: atuação da enfermeira na perspectiva da promoção da saúde - Gurgel, Maria Glêdes Ibiapina (2008)
The World Health Organization (WHO) defines the age of adolescence as being between 10 and 19 years and the Statute of the Child and Adolescent (ECA) between 12 and 18 years. It is a stage of life that occur the sexual maturation, the fierce of family conflicts and formation and crystallization of attitudes, values and behaviors. Dealing with such situations requires of health teams an integrated approach, including the prevention of adolescent pregnancy. The national health policy for the adolescent, offers a basic guidelines to guide the implantation and / or implementation of actions and health services to adolescents and young people in integral, participatory and decisive way. Recognizes as a challenge the access of adolescents to quality services, with the understanding of the meaning and importance of economic, social and cultural fields that permeate the lives of this group. The study aimed to examine the practices of nurses in promoting health of adolescents, adopted in the Strategy of Family Health (SFH), aimed the prevention of teenage pregnancy. The method used was descriptive and exploratory, with a qualitative approach and had as investigative environment eight Family Health Centers (CSF) of the city of Fortaleza. The population consisted of nurses linked to the SFH, which the researched group consisted of eight participants. The technique used to collect data was the focus group and as a method of data analysis, the discursive practices and production of meaning in everyday life, having as resources, the maps of association of ideas. The results of the discussions were arranged in columns on topics and categories of analysis, previously defined as: Conception of health, Conception of health promotion and Practice / practices in the prevention of teenage pregnancy. The study points as a result the nurses concepts the health and health promotion between the traditional concept (prevention of the disease) and broader, based on health promotion and the planning of actions to promote the health of adolescents in the prevention of teenage pregnancy has been most often on campaigns, without focusing on the individual on its integrality; weakness in the organization of the reference and cross-reference system, the inter-sector actions are incipient, there is need to expand the knowledge, by the nurses, about public policies focused on the adolescent. The actions of health promotion permeate the nursing consultation and the activities in groups, emphasizing the reception and ethics as devices that help to foster an environment conducive to the health of adolescents. It is recommended that the guidelines proposed by the Health Policy of adolescent be strengthened, in the municipal level, in order to provide the nurse, conditions to promote inter-sector and interdisciplinary actions of sex education in the context of prevention of early pregnancy, which includes the family, school and community, contributing to the pursuit of a safer and more responsible sexuality